Sir Purshottamdas Thakurdas - Visual History of Business and Trade in India (2023)
Sir Purshottamdas Thakurdas was regarded as the "doyen of the business community". He held significant positions in numerous organizations including the Bombay Indian Merchants' Chamber and Bureau (later renamed the Indian Merchants' Chamber), the East India Cotton Association, and the Indian Currency League. He played a leading role, along with Ghanshyamdas Birla, in the formation of the Federation of Indian Chambers of Commerce and Industry (FICCI) in 1927.